2022
DOI: 10.4155/fmc-2022-0063
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Tools of Synthetic Biology Applied to Drug Discovery and Production

Abstract: Although synthetic biology is an emerging research field, which has come to prominence within the last decade, it already has many practical applications. Its applications cover the areas of pharmaceutical biotechnology and drug discovery, bringing essential novel methods and strategies such as metabolic engineering, reprogramming the cell fate, drug production in genetically modified organisms, molecular glues, functional nucleic acids and genome editing. This review discusses the main avenues for synthetic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…This interdisciplinary approach combines the precision of engineering with the complexity of biological systems to create innovative solutions for drug discovery and production. Pavlova et al (2022) discuss the application of synthetic biology tools in pharmaceutical biotechnology and drug discovery. Synthetic biology introduces novel methods such as metabolic engineering, reprogramming cell fate, and drug production in genetically modified organisms.…”
Section: The Interplay Of Biology and Engineering In Drug Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This interdisciplinary approach combines the precision of engineering with the complexity of biological systems to create innovative solutions for drug discovery and production. Pavlova et al (2022) discuss the application of synthetic biology tools in pharmaceutical biotechnology and drug discovery. Synthetic biology introduces novel methods such as metabolic engineering, reprogramming cell fate, and drug production in genetically modified organisms.…”
Section: The Interplay Of Biology and Engineering In Drug Developmentmentioning
confidence: 99%
“…These techniques enable the creation of molecular glues, functional nucleic acids, and genome editing, reshaping drug development and production. The authors posit that synthetic biology will have an impact on drug development comparable to the advances in organic chemical synthesis in the 20th century, highlighting the transformative potential of this interdisciplinary field (Pavlova et al, 2022). Zhao et al ( 2023) explore synthetic biology-inspired cell engineering in diagnosis, treatment, and drug development.…”
Section: The Interplay Of Biology and Engineering In Drug Developmentmentioning
confidence: 99%
“…It is known as the thiamine pyrophosphate (TPP) riboswitch and regulates gene expression via alternative splicing [13,14]. Recent research has shown that riboswitches may be promising novels targets for antibacterial drug discovery [12,15,16]. Bacterial riboswitches are mostly located in the untranslated regions of different mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Methods of synthetic biology can be employed not only to develop but also to produce new antibiotics. 20,21 ■ MATERIALS AND METHODS Bioinformatics Databases. The aptamer sequences of the TPP riboswitch in several bacteria were obtained from the RSwitch https:// penchovsky.atwebpages.com/applications.php?page=58 databases.…”
Section: ■ Introductionmentioning
confidence: 99%
“…When these two pathways are inhibited, the bacteria cannot survive. Methods of synthetic biology can be employed not only to develop but also to produce new antibiotics. , …”
Section: Introductionmentioning
confidence: 99%